2023
DOI: 10.1002/ecm.1567
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics structure plankton communities and interactions in a freshwater tidal estuary

Abstract: Drivers of phytoplankton and zooplankton dynamics vary spatially and temporally in estuaries due to variation in hydrodynamic exchange and residence time, complicating efforts to understand controls on food web productivity. We conducted approximately monthly (2012–2019; n = 74) longitudinal sampling at 10 fixed stations along a freshwater tidal terminal channel in the San Francisco Estuary, California, characterized by seaward to landward gradients in water residence time, turbidity, nutrient concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(167 reference statements)
1
0
0
Order By: Relevance
“…However, we found net biotic and abiotic effects to be of comparable magnitude. We also found that driver strength varied by region and timescale, in agreement with prior studies that found variability in the relative importance of biotic and abiotic drivers with spatiotemporal context (Guinder et al, 2017; Smits et al, 2023). From a management perspective, the relative importance of abiotic drivers is important because environmental factors (i.e., flow and turbidity) can often be manipulated directly, for example, through freshwater flow manipulation (Hemraj et al, 2017; Sommer, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…However, we found net biotic and abiotic effects to be of comparable magnitude. We also found that driver strength varied by region and timescale, in agreement with prior studies that found variability in the relative importance of biotic and abiotic drivers with spatiotemporal context (Guinder et al, 2017; Smits et al, 2023). From a management perspective, the relative importance of abiotic drivers is important because environmental factors (i.e., flow and turbidity) can often be manipulated directly, for example, through freshwater flow manipulation (Hemraj et al, 2017; Sommer, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Landward zone transitions from the more marineinfluenced seaward areas to the terrestrial realm; it experiences unique conditions that shape the phytoplankton dynamics. Furthermore, the hydrology of the landward zone, shaped by tides and freshwater inflow, plays a role in determining phytoplankton distribution (Smits et al 2023). One of the defining features of the landward zone is its proximity to terrestrial inputs, which can bring freshwater and nutrients into the ecosystem (Ward et al 2020).…”
Section: Discussionmentioning
confidence: 99%